Hearing Loss in Patients with Chronic Kidney: Our Experience in a Tertiary Care Hospital in Nepal - Basnet, Meenakshi; Shrestha, Shailendra; Neupane, Bijay; Aryal, Gyan Raj (Birat Journal of Health Sciences, 2020)
Introduction: Patients with chronic kidney diseasesuffer from sensorineural hearing loss as a complication.The prevalence, type and degree of hearing loss along with the associated factors like age, electrolyte imbalance, hypertension, diabetes, duration and stage of CKD were studied. Methodology:This was a prospective cross-sectional study conducted in the department of Otorhinolaryngology and Nephrology at Nobel Medical College & Teaching Hospital, Kanchanbari, Biratnagar, Nepal from1st August 2018 to 30th September 2019.After thorough history taking, clinical & biochemical examinations, all patients underwent Tuning fork test and Pure tone audiometry. CKD was staged according to the eGFR. Data were stored in excel spreadsheet and analysis was done using the SPSS software (version 21) Result: Out of 150 patients,the ratio of male to female was 1.2:1. The mean age of the patients was 44.04 ± 10.524 years. 68 (45%) patients had CKD stage V with a median duration of 24 (18 – 36) months. The prevalence of hearing loss was found to be 83 (55.3%), most of them in bilateral ear (58%). The staging of CKD had a significant association with the prevalence of hearing loss and its severity. The duration of the illness had a strong association with hearing loss. Conclusion: This study shows that sensorineural hearing loss prevails in the patients suffering from CKD, which increases with age, duration of CKD, presence of comorbidities like hypertension, diabetes and level of serum urea and creatinine. However, it could not establish diabetes and electrolyte as a potential risk factor for developing hearing loss from CKD.